Thermodynamic analysis of the apple drying process - Akpinar, EK; Midilli, A; Bicer, Y (Professional Engineering Publishing Ltd, 2005)
This paper is concerned with thermodynamic analysis of the process of single-layer drying of apple slices by means of a cyclone-type dryer. Using the first law of thermodynamics, energy analysis was performed to estimate the ratios of energy utilization throughout the drying process. Exergy analysis was carried out to determine exergy losses during the drying process by applying the second law of thermodynamics. It was concluded that the exergy losses increased with increasing energy utilization in both trays and the drying chamber. Values of the energy utilization ratio (EUR) of the drying chamber varied in the range 0-41.64 per cent depending on the drying conditions. The most exergy losses took place on the first tray (EUR = 0-21.06 per cent) during the drying of apple slices. It is emphasized that apple slices are sufficiently dried in the range 60-80 degrees C with 20-10 per cent relative humidity and a drying air velocity of 1.5 m/s over a 3.33-5.33 h period in spite of exergy losses of 0-1.243 kj/s (EUR = 0-34.72 per cent).
Keywords: drying; thermodynamic analysis; energy and exergy; apple